Autorzy:Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2015
Wykonhaj działania. a) (3√2+2√5)(3√2-2√5)4.57 gwiazdek na podstawie 7 opinii

a)

`(3sqrt2+2sqrt5)(3sqrt2-2sqrt5)=(3sqrt2)^2-(2sqrt5)^2=9*2-4*5=18-20=(-2)`

b)

`(3sqrt7-sqrt2)^2=(3sqrt7)^2-2*3sqrt7*sqrt2+(sqrt2)^2=9*7-6sqrt14+2=`

`=63+2-6sqrt14=65-6sqrt14`

c)

`(sqrt6+2sqrt3)^2=(sqrt6)^2+2*sqrt6*2sqrt3+(2sqrt3)^2=6+4sqrt18+4*3=`

`=6+4sqrt(2*9)+12=6+4*3sqrt2+12=18+12sqrt2=6(3+2sqrt2)`

d)

`(2root(3)3+3root(3)2)^2=` `(2root(3)3)^2+2*2root(3)3*3root(3)2+(3root(3)2)^2=4root(3)9+12root(3)6+9root(3)4`